Performance of four full-scale artificially aerated horizontal flow constructed wetlands for domestic wastewater treatment - Butterworth, Eleanor; Richards, Andrew; Jones, Mark; Mansi, Gabriella; Ranieri, Ezio; Dotro, Gabriela; Jefferson, Bruce (Cranfield University, 2016)
A comparison of the performance of four full-scale aerated horizontal flow constructed wetlands was conducted to determine the efficacy of the technology on sites receiving high and variable ammonia loading rates not yet reported in the literature. Performance was assessed in terms of ammonia and solids removal, hydraulic conductivity and mixing patterns. The capability of systems to produce ammonium effluent concentrations <3 mgNH4 + -N/L was observed across all sites in systems receiving variable loadings between 0.1 and 13.0 gNH4 + -N/m2 /d. Potential resilience issues were observed in relation to response to spike loadings posited to be due to an insufficient nitrifying population within the beds. Hydraulic conductivity and flow mixing patterns observed suggested deterioration of the reactor effective volume over time. Overall, the study demonstrates the efficacy of the technology where ammonium removal is required on small sites receiving high and variable flow rates, with adequate removal of organics and solids, but no significant benefit to the long term hydraulics of the system.
Keywords: aeration; clogging; dissolved; oxygen; nitrification; treatment wetlands